Legal Certainty of Donation of Debt Payment Obligations (PKPU) As a Means of Resolving Non-Load Loans Related to the Banking Relaxation Program during the Covid-19 Pandemic - Akbar, Raihan Imam Cahya; Noer, Yuhelson M; Tondy, Cicilia Julyani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Covid-19 pandemic has had an impact on the economy in Indonesia. The government says that Covid-19 is a non-natural national disaster. The application of social distancing is a way to deal with the spread of the covid-19 virus, but with the presence of social distancing this makes the weakening of the economy that has an impact on business actors in Indonesia. Delay of debt payment obligation (PKPU) provides the purpose of the debtor or creditor applying for a delay in debt payment obligations (PKPU). In addition, the government also provides banking relaxation regulations to support companies that are affected by covid-19. The purpose of this research is to find out the implementation of PKPU supported by relaxation of banking issued by the government to overcome bad credit and know legal certainty in the implementation of PKPU with the relaxation of banking. This research is a normative juridical law research. The result of this research is the implementation of PKPU with the relaxation of banking has been running in accordance with Law No. 37 of 2004 and OJK No. 11 / OJK.03 / 2020. But for waivers that apply in accordance with OJK No. 11 /ṔOJK.03/2020 only applies to business actors who have a loan ceiling to Bank Negara only 03 /2020. But for waivers that apply in accordance with OJK No. 11 /ṔOJK.03/2020 only applies to business actors who have a loan ceiling to Bank Negara only 03 / 2020. But for waivers that apply in accordance with OJK No. 11 /ṔOJK.03/2020 only applies to business actors who have a loan ceiling to Bank Negara only.